Numerical and Experimental Analysis of Scoliosis Brace - Slawomir Grycuk; Piotr Mrozek (Research Highlights in Science and Technology Vol. 9, 2023)
The main purpose of the work was to recognize the working scheme of the structure of a brace and then to identify the possibilities of optimization of the orthosis construction. This chapter presents the results of numerical simulations of the Boston-type orthosis using the finite element method (FEM) in the Ansys Workbench environment. Scoliosis is a clinical condition marked mostly by a lateral curvature of the spine. Moderate cases of adolescent idiopathic scoliosis (AIS) are typically treated through conservative methods which try to naturally correct scoliosis during the growth of the patients. A common conservative treatment is to use orthotic brace structure. The geometric model was developed based on the results of digitisation performed by means of a three-dimensional (3D) optical scanner. A test stand for measurement of the brace’s field of displacements, utilising a laser electronic speckle pattern interferometer (ESPI), was used to experimentally verify the FEM model. Particular focus was placed on applying the loads and boundary conditions employed in the numerical calculations during the experimental testing. As a result, there was a relative difference of 0.6% or so between the center displacements of orthoses as estimated experimentally and numerically. Taking an approach in the direction defined in this way, a conventional analysis method of the FEM modelling results output was used, consisting of the calculation of the von Mises stress distribution at loads equal in order to the magnitude of the common correction loads, imposed in accordance with an elementary “three-point system”. The experimentally verified FEM model was used to determine the force flow lines characteristic of the brace, indicating the general working method of the brace’s structure. The main components of the orthoses were discovered, together with the loads they carried for straightening the spine and the locations of spots that required little effort to participate in the orthoses’ principal therapeutic function. The outcomes enable the suggestion of strategies for mechanical optimization of the brace’s design.